Alcívar Macías,Willington Paul(2023)Evaluación del pH del agua en la eficacia de diferentes dosis de Glufosinato de amonio aplicado en el cultivo de maíz (Zea mays L.).Quevedo.UTEQ.80p. - Alcívar Macías , Willington Paul (2023)
Corn is a profitable crop in its production when it is managed under adequate conditions. Efficient weed control is essential for its production, since they compete for light, nutrients and water, causing a reduction in yield and grain quality. The research was carried out in the facilities Campus Experimental “La María”, de la Universidad Técnica Estatal de Quevedo, with the purpose of evaluating the pH of the water in the efficacy of different doses of glufosinate ammonium applied in the corn crop. (Zea mays), and thus determine the control provided by the treatments. A completely randomized block design (DBCA) with ten treatments and three repetitions was used. The variables evaluated were subjected to an Analysis of Variance, and a Tukey test was performed to identify the differences between treatments. The treatment with 200 g of a.i. /ha + pH 8.5 presented a greater control of the weeds (97.5 %) and a lower index of phytotoxicity in the crop (3.25%). In the treatment with 200 g of a.i / ha + pH 3, the plant height was higher, and in the treatment with 250 g of a.i / ha + pH 8.5, it obtained a greater ear weight, diameter, length and number of rows. Weed control costs depended on the amount of a.i. used, with 200 g a.i./ha being the most effective in control, with fewer effects on the crop.